Evaluation of the Implementation of the Performance-Based Capitation Policy (KBK) at the Merial Health Clinic of DKI Jakarta City in 2020 - Umakaapa, Muktamar; Sjaaf, Amal Chalik (Journal of Indonesian Health Policy and Administration, 2021)
To improve the quality of health services at Primary Health Care (FKTP) in implementing the National Health Insurance Program in Indonesia, the government has issued a performance-based capitation payment (KBK) policy at the FKTP. This study aims to evaluate the performance-based capitation payment policy in Merial Health clinic from the aspects of effectiveness, efficiency, facilities and infrastructure, availability of human resources, adequacy, and legal compliance. This study performed in-depth interviews and document reviews. The results showed that the effectiveness of the policy has been optimal but is still constrained by the socialization of the KBK policy and visits to health numbers for BPJS Health participants. The efficiency of the KBK policy has been running optimally in increasing the capitation income of the Merial Health clinic. The adequacy of the policy is as expected because it improves the quality of health services. The availability of human resources is in accordance with the BPJS Health provider standards. Facilities and infrastructure are in accordance with cooperation rules as a BPJS Health provider. Legal compliance has been running optimally because it has met the applicable requirements. The study concludes that the implementation of the performance-based capitation policy at the Merial Health clinic has been running optimally.